2019
DOI: 10.5965/223811711842019438
|View full text |Cite
|
Sign up to set email alerts
|

Morfofisiologia de plantas de couve manteiga sob concentrações de húmus líquido

Abstract: Morfofisiologia de plantas de couve manteiga sob concentrações de húmus líquidoMorphophysiology of plants of butter collard as function of liquid humus concentration RESUMO A couve manteiga (Brassica oleracea var. acephala L.) pertence à família Brassicaceae e vários estudos têm demonstrado as variações ocorridas nas trocas gasosas entre as plantas e a atmosfera, em virtude de práticas ou de tratamentos aplicados às culturas agrícolas, com consequentes estados de estresse e reflexos negativos sobre os processo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Segundo estudo realizado por Rocha et al (2019) [20], o estresse pode ser causado devido ao ambiente de cultivo, sendo necessário conhecer tanto a morfologia quanto as variáveis fisiológicas da planta como os pigmentos fotoprotetores. A clorofila a, por exemplo, é um pigmento de suma importância na planta pois apresenta-se na fase fotoquímica, enquanto os demais pigmentos auxiliam na absorção de luz e na transferência da energia para os centros de reação [21].…”
Section: Resultsunclassified
“…Segundo estudo realizado por Rocha et al (2019) [20], o estresse pode ser causado devido ao ambiente de cultivo, sendo necessário conhecer tanto a morfologia quanto as variáveis fisiológicas da planta como os pigmentos fotoprotetores. A clorofila a, por exemplo, é um pigmento de suma importância na planta pois apresenta-se na fase fotoquímica, enquanto os demais pigmentos auxiliam na absorção de luz e na transferência da energia para os centros de reação [21].…”
Section: Resultsunclassified
“…The gs decreased with the increase of calcium silicate doses at the full flowering stage, at 58 DAT ( Figure 2B), with no significant effect for this variable in the other evaluations. This reduction may have occurred due to some momentary stress, such as an increase in temperature, as gs is a punctual measure and will determine the number of stomata opened at the time of reading (Rocha et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that Ci presented a negative correlation with WUE, iWUE, and ACi (Table 2), which influenced the stoma opening and closing, the entry and exit of CO2, the loss of water, and consequently, its fixation in the formation of new carbohydrates. Lower Ci values stimulate stoma closure with a consequent decrease in the rate of CO2 assimilation (Rocha et al, 2019).…”
Section: Datmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in Ci during the vegetative stage for the cv. Princesa was associated with an increase in A rate during this phase (Table 3); this may have been a strategy to stimulate stomatal opening, the entry of CO 2 and consequently carbon fixation for carbohydrate production (Rocha et al, 2019), given that this phase demonstrated the highest CEi for the production of photoassimilates in the growth and development of apple trees (Table 3).…”
Section: Medium Squaresmentioning
confidence: 99%